SOCIOLINGUISTICS IN THE 21ST CENTURY: CHALLENGES AND CURRENT ISSUES (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
Sociolinguistics in the 21st century has entered a new phase marked by rapid globalization, digital communication, migration, and cultural diversity. The study of language in its social context today faces numerous challenges, including the preservation of minority languages, the rise of English as a global lingua franca, the influence of social media on language use, and issues of linguistic identity in multicultural societies. Moreover, technological advancement has reshaped patterns of communication, raising new questions about language variation, code-switching, and online discourse. This paper highlights current issues in sociolinguistics such as language and power, language policy, multilingualism, and the sociolinguistic implications of artificial intelligence. Addressing these challenges is essential for understanding the evolving relationship between language, society, and identity in the modern world.